Remediation technologies for soils and groundwater - Bhandari, Alok (American Society of Civil Engineers, 2007)
Sponsored by the Remediation Technologies for Soils and Groundwater Task Committee of the Environmental Council of the Environmental and Water Resources Institute of ASCE. This report provides a comprehensive and thorough overview of conventional engineered processes and technologies used for the remediation of contaminated sites. Site remediation is a complex and costly process that aims to restore adversely affected land and groundwater resources to environmentally sustainable conditions. With extensive illustrations, tables, and case studies, this book has a simple-to-follow writing style that makes it appropriate for use as a classroom text as well as a reference for practitioners.